PENERAPAN ASUHAN KEPERAWATAN KELUARGA DENGAN INTERVENSI EDUKASI KESEHATAN METODE SMALL GROUP DISCUSSION DAN GAME SIMULASI UNTUK MENINGKATKAN PENGETAHUAN MENGENAI PERILAKU PENCEGAHAN HIV/AIDS PADA REMAJA DI RT.008/09 GEDONG - Dinna Wahyuni (2022)
The level of knowledge of adolescents about HIV/AIDS in Indonesia is still in the not good enough category, namely 48.9%. The lack of information obtained by these teenagers results in the lack of knowledge of adolescents regarding HIV/AIDS, therefore this will have an impact, namely the high number of cases of HIV/AIDS. Efforts that can be made to increase adolescent knowledge are by conducting health education. One of the educational methods that can be used is the small group discussion method and the simulation game: snakes and ladders. The purpose of implementing this nursing care is to determine the effectiveness of health education using the small group discussion method and simulation game: snake and ladder to increase adolescent knowledge about HIV/AIDS prevention behavior. The implementation of this health education was carried out for three consecutive days. The results of the implementation of the health education intervention using the small group discussion method and simulation game: snakes and ladders showed that after three days of health education, the clients managed and resumed clients increased. The results of the pre-test on patients managed before the intervention was carried out with 6 correct questions out of 20 questions, after the intervention was carried out, it was seen from the post test results the client answered 18 questions correctly out of 20 questions. The conclusion from the application of nursing care is that it is proven to be effective in increasing knowledge in adolescents. Community nurses are expected to be able to make this education as an option to overcome the problem of knowledge deficit in adolescents.